RSS-TOA based localization algorithm in non-line-of-sight environment - Zhigang LU; ·ouming LI; Xianghong JIA; Shengming CHANG; Xiaoli WANG (Dianxin kexue)
The existence of non-line-of-sight (NLOS) error can degrade the positioning performance in wireless sensor network localization system,especially in indoor localization.To overcome the localization error caused by NLOS propagation,a localization algorithm was proposed based on received signal strength (RSS) and time-of-arrival (TOA).Firstly,a non-convex optimization problem was established based on RSS and TOA.Then,the original non-convex optimization problem was transformed into a convex optimization problem through the second-order cone relaxation technique,therefore a sub-optimal solution to the original problem could be obtained efficiently.Finally,computer simulation results show that the proposed method can provide higher estimation accuracy and better performance.